Pulmonary fibrosis through the prism of NLRP3 inflammasome: mechanistic pathways and prospective therapeutic innovations - Wang, Mengxue; Xie, Yuanyuan; Cao, Yuqing; Yu, Bing; Dai, Qingqing (Frontiers in Immunology, 2025)
Pulmonary fibrosis is a disease that severely affects the patients’ life quality, characterized by lung tissue remodeling and functional impairment. Recent research has found that the NLRP3 inflammasome plays an important role in the pathogenesis of pulmonary fibrosis. Although existing researches have revealed the potential role of NLRP3 in pulmonary fibrosis, many mysteries still remain regarding its specific mechanisms and clinical applications. This article aims to review the mechanisms of action of NLRP3 in pulmonary fibrosis, related signaling pathways, and the latest research progress on its potential as a therapeutic target, in hopes of providing new ideas and directions for future clinical treatment.